1994
DOI: 10.1161/01.cir.89.1.366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcitonin gene-related peptide on coronary microvessels and its role in acute myocardial ischemia.

Abstract: CGRP preferentially dilates the coronary arterial microvessels > 100 microns in diameter but has only a small effect on those < 100 microns. Endogenous CGRP does not modulate the tone of coronary arterial microvessels during acute myocardial ischemia in beating canine hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…However, the receptor density and the efficiency of coupling between the receptor and the stimulus-response mechanisms in the human subcutaneous arteries will influence the maximal response to CGRP in any case. In the present study, we have shown that the maximal response and the sensitivity to CGRP is inversely related to the calibre of human subcutaneous arteries, which is in concert with the previous findings in the coronary arteries of rat (Sheykhzade & Nyborg, 1998), dog (Sekiguchi et al, 1994) and human (McEwan et al, 1986), and also in human cerebral arteries (Sams et al, 2000). Our present results therefore indicate that this observation can be explained either by an increase in CGRP 1 -receptor density or by increased efficiency of receptor-effector coupling downstream of the vasculature.…”
Section: Receptor Reserve and Calibre Dependency Of Cgrp-induced Relasupporting
confidence: 92%
“…However, the receptor density and the efficiency of coupling between the receptor and the stimulus-response mechanisms in the human subcutaneous arteries will influence the maximal response to CGRP in any case. In the present study, we have shown that the maximal response and the sensitivity to CGRP is inversely related to the calibre of human subcutaneous arteries, which is in concert with the previous findings in the coronary arteries of rat (Sheykhzade & Nyborg, 1998), dog (Sekiguchi et al, 1994) and human (McEwan et al, 1986), and also in human cerebral arteries (Sams et al, 2000). Our present results therefore indicate that this observation can be explained either by an increase in CGRP 1 -receptor density or by increased efficiency of receptor-effector coupling downstream of the vasculature.…”
Section: Receptor Reserve and Calibre Dependency Of Cgrp-induced Relasupporting
confidence: 92%
“…The present findings with intravenous and intra-atrial CGRP extend these previous findings by demonstrating no effect of CGRP receptor antagonism on coronary flow during cardiac stress produced by rapid atrial pacing and coronary stenosis. One previous study in anesthetized dogs reported no effect of topically administered CGRP onto the left ventricular surface on coronary artery microvessel diameter before and at 10 min after LAD coronary artery occlusion (Sekiguchi et al, 1994). The present study extends the latter findings by demonstrating no effect on coronary flow with systemically administered CGRP (8-37) during both coronary constriction and atrial pacing, as well as demonstrating no effect on a functional measure of ischemia severity.…”
Section: Discussionsupporting
confidence: 81%
“…In vitro, CGRP potently relaxed human and dog epicardial coronary arteries (Gulbenkian et al, 1993;Quebbeman et al, 1993). In vivo, exogenous CGRP exerted systemic depressor (Franco-Cereceda et al, 1987;Shen et al, 2001) and coronary vasodilator effects with greater effect on coronary diameter observed in larger versus smaller vessels in both species (Ludman et al, 1991;Sekiguchi et al, 1994). These observations support dog as a relevant species for assessing CGRP antagonist cardiovascular effects in relation to similarity to human.…”
Section: Discussionmentioning
confidence: 88%
“…These neuropeptides produce coronary vasodilation and negative inotropic and chronotropic effects, which would be expected to limit the deleterious consequences of ischemia on the myocardium (35). Our previous study (45) has shown that I/R injury caused more profound impairment in terms of LVEDP, LVDP, and CF in TRPV1 Ϫ/Ϫ than in WT hearts, indicating that TRPV1 protects against I/R injury.…”
Section: Discussionmentioning
confidence: 95%